KETERAMPILAN MEMBACA DAN MENULIS ANAK DINI DI DESA CIPELANG - Egi Adi Saputra; Alinda Alinda; Fahmi Ardiansyah Ramli (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2023)
This service aims to determine the role of the early literacy movement in the family and to determine the level of basic literacy skills, especially reading and writing in early childhood in Cipelang Village, Cijeruk District, Bogor Regency. The service method uses survey methods, mentoring, and reading and writing ability tests carried out on children aged 4-6 years with pre-test and post-test analysis. The results of the service show that before the early literacy movement education was carried out, it could be seen that the condition of early childhood literacy was 27.5% of the total sample of 10 children and after the early childhood literacy education was carried out it increased to 92.5% of the total sample of 10 children. . In the sense that children and parents feel enthusiastic about providing learning facilities, providing children's reading materials, parents are enthusiastic about reading stories to children so that young children have a high interest in reading. Meanwhile, the reading and writing skills of young children before assistance was provided, only 31.9% of the total of 10 young children could read and write. After assisting, the reading and writing ability of young children increased to 85.4%. In other words, this service has an impact on increasing the early literacy movement and improving the reading and writing abilities of young children. So the recommendation given is the need for active involvement of the community and various related parties to encourage the implementation and improvement of the quality of the early literacy movement for young children in Cipelang Village.